Evolution of plastid gene rps2 in a lineage of hemiparasitic and holoparasitic plants: Many losses of photosynthesis and complex patterns of rate variation - dePamphilis, Claude W. (The National Academy of Sciences of the USA, 1997)
The plastid genomes of some nonphotosynthetic parasitic plants have experienced an extreme reduction in gene content and an increase in evolutionary rate of remaining genes. Nothing is known of the dynamics of these events or whether either is a direct outcome of the loss of photosynthesis. The parasitic Scrophulariaceae and Orobanchaceae, representing a continuum of heterotrophic ability ranging from photosynthetic hemiparasites to nonphotosynthetic holoparasites, are used to investigate these issues. We present a phylogenetic hypothesis for parasitic Scrophulariaceae and Orobanchaceae based on sequences of the plastid gene rps2, encoding the S2 subunit of the plastid ribosome. Parasitic Scrophulariaceae and Orobanchaceae form a monophyletic group in which parasitism can be inferred to have evolved once. Holoparasitism has evolved independently at least five times, with certain holoparasitic lineages representing single species, genera, and collections of nonphotosynthetic genera. Evolutionary loss of the photosynthetic gene rbcL is limited to a subset of holoparasitic lineages, with several holoparasites retaining a full length rbcL sequence. In contrast, the translational gene rps2 is retained in all plants investigated but has experienced rate accelerations in several hemi- as well as holoparasitic lineages, suggesting that there may be substantial molecular evolutionary changes to the plastid genome of parasites before the loss of photosynthesis. Independent patterns of synonymous and nonsynonymous rate acceleration in rps2 point to distinct mechanisms underlying rate variation in different lineages. Parasitic Scrophulariaceae (including the traditional Orobanchaceae) provide a rich platform for the investigation of molecular evolutionary process, gene function, and the evolution of parasitism.